ANALYSIS OF STUDENTS' ERRORS OF CLASS XI SMKN 2 PALU IN SOLVING MATRIX STORY PROBLEMS USING NEWMAN - Ni Luh Ermayanti; Gandung Sugita; Alfisyahra Alfisyahra; I Nyoman Murdiana (JME (Journal of Mathematics Education), 2024)
The purpose of this study was to obtain a description of the mistakes made by class XI students of SMK Negeri 2 Palu in solving word problems on matrix material based on Newman's stages. The type of research used is qualitative research. The research design consists of planning, implementation and completion stages. The research subjects were 3 students of class XI at SMK Negeri 2 Palu. The results of this study indicate that DE subjects experienced errors at the stages of understanding the problem, the stage of transformation, the stage of processing skills, and the stage of writing the final answer. The HR subject experienced errors at the stage of transformation, stage of process skills and stage of writing the final answer. The RW subject experienced errors at the stages of understanding the problem, the transformation stage, the process skills stage, and the final answer writing stage. Therefore, it was concluded that all subjects did not experience errors in the question reading stage.